How to improve reading comprehension: an overview of types of pedagogical interventions - Antić, Slobodanka; M. Stevanović, Jelena (Studies in Teaching and Education, 2024)
Literacy, according to contemporary understanding, is a situational, complex competence integrated into various social practices. Therefore, we view it as multiple literacies with numerous dimensions—linguistic, mathematical, scientific, political, economic, media-related, and so on. However, multiple literacies can only be achieved through the development of linguistic literacy, which serves as the mediator and moderator of all other literacies. The most researched aspect of linguistic literacy is reading comprehension. The aim of this paper is to categorize and systematize various pedagogical interventions that contribute to the development of reading comprehension, which is the foundation of all meaningful learning. The analysis and organization of empirical findings, programs, and practical endeavors were based on two criteria: who is the primary actor or most responsible for a particular type of intervention, and what is the focus of the intervention to be implemented. Our analysis identified six different types: psychological-pedagogical-linguistic interventions on the text itself; support for the development of students' cognitive competencies related to reading; support for the development of students' personality and affective competencies; innovations in teaching/learning methods; interventions in the learning environment; and interventions in the domain of educational policies. The paper provides descriptions and examples for each type of pedagogical intervention and concludes that the synergy of all is the most effective way to develop literacy in children and youth.
Keywords: language literacy, pedagogical interventions for literacy development; teaching reading comprehension, development of reading competences, functional literacy